2017
DOI: 10.14233/ajchem.2017.20580
|View full text |Cite
|
Sign up to set email alerts
|

Four Factor Surface Response Optimization of Ethyl Palmitate from Terminalia cattapa L. Kernel Oil

Abstract: INTRODUCTIONEthyl palmitate is the ester derivatives of palmitic acid which is a saturated fatty acid. Chemical formula of this compound is C 18 H 36 O 2 . It is a colorless solid with a wax-like odor. Esters are important organic compounds with increasing number of commercial applications [1]. Ethyl palmitate are infrequent found in the nature, except the base material synthesized from saturated fatty acids, such as palmitic acid.Palmitic acid contained in palm oil (39.2-45.8 %) [2], corn oil 8.0-12.0 %, soy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The run temperature profile was 2 min at 40 , 8 /min at 280 , and 5 min at 280 . A flame ionization detector FID was used at 300 15 .…”
Section: Optimization Of Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The run temperature profile was 2 min at 40 , 8 /min at 280 , and 5 min at 280 . A flame ionization detector FID was used at 300 15 .…”
Section: Optimization Of Temperaturementioning
confidence: 99%
“…At the temperature of 50 to 70 , there was a decrease in the amount of reaction product formed. This occurred because enzymes are denatured at high temperatures 15,23 . Islam et al 24 reported that lipase is very active at temperatures of 30-40 , while at temperatures above 50 , the enzyme may be deactivated 25 .…”
Section: Optimization Of Temperaturementioning
confidence: 99%
“…Lipase is able to catalyze a reaction in a short time, at low temperature and low pressure. 14,15 In this study, the optimization reactions have been performed to synthesize fatty dietanolamide from nyamplung kernel oil with the following variables: time reaction, temperature, ratio substrate and amount of enzyme. The enzyme used as a catalyst is the immobilized enzyme from Thermomyces lanuginosus or Lipozyme TLIM.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the enzymatic synthesis method is a specific reaction, mild reaction condition, environmentally friendly process and simple purification process. 11,12 The other studies of enzymatic synthesis of FHA is the tiohydroxamic synthesis of palm oil with lipase catalyst, 7 the enzimatic synthesis of FHA of coconut oil, 6 and the synthesis of fatty phenyl hydroxamic acids of coconut oil with the lipase enzymes. 8 From a few studies that have been mentioned above, the raw material use edible oil.…”
Section: Introductionmentioning
confidence: 99%
“…11,13 Ketapang oil also has a characteristic physical-chemical properties so that it is suitable to be used as a base materials. 11, 12,13 For that reason, ketapang kernel oil has the potential to be used as raw material of FHA synthesis.…”
Section: Introductionmentioning
confidence: 99%